ON THE UNIQUENESS OF ALGEBRAIC CURVES - Bayramyan, V.H.; Hakopian, H.A.; Toroyan, S.Z. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2015)
It is well-known that $N -1$ $n$-independent nodes uniquely determine curve of degree $n$, where $N = (1/2)(n + 1)(n + 2)$. We are interested in finding the minimal number of $n$-independent nodes determining uniquely curve of degree $k≤1$. In this paper we show that this number for $k=n-1$ is $N-4$.
Keywords: polynomial interpolation, independent nodes, algebraic curves